Estimation of thermodynamic characteristics for comprehensive dairy food processing plant: An energetic and exergetic approach. (1st March 2020) - Singh, Gurjeet; Tyagi, V.V.; Singh, P.J.; Pandey, A.K.
Abstract: India produces and consumes an array of traditional and modern dairy products. The value added milk derivatives such as cream, butter, ghee, yogurt, ice cream and other condensed forms of milks etc, forms 54% of the total dairy consumption with an annual energy consumption of 0.4 Mtoe in the year 2018. In view of 3.6% annual growth of this sector, the exergetic estimation of comprehensive dairy processing plant which primarily includes milk pasteurisation, cream pasteurisation and ghee manufacturing units are highly imperative for better utilization of energy resource. The present study determined first and second law performances, exergy destruction and exergy improvement potential in specific values for complete dairy processing plant consisting of aforementioned units; as 90%, 82.13%, 612.77 kJ/kg and 410.12 kJ/kg respectively. The highest contribution to specific exergy destruction was found at ghee production unit (410.10 kJ/kg) followed by cream pasteurisation unit (117.68 kJ/kg). Similarly specific exergy improvement potential was reported to be highest in ghee production unit (291.14 kJ/kg) followed by cream pasteurisation unit (74.31 kJ/kg). The total amount of electrical and thermal energy consumption was ascertained to be 322.25 kW and 171.64 kW respectively. Highlights: Thermodynamic behaviour of dairy plant was assesed in present work. Universal exergy efficiency of entire plant was calculated to be 82.13%. The specific magnitude of exergy improvement potential of plant was 410.12 kJ/kg. Total amount of steam consumption in the plant was estimated to be 701.28 kg/h. Total electrical and thermal exergy consumptions were 322.25 kWh and 171.64 kWh.